Transfer of skills acquired through Cognitive Orientation to daily Occupational Performance (CO‐OP) approach in children with executive functions deficits following acquired brain injury. - Vezinat, Clarisse; Lebrault, Hélène; Câmara‐Costa, Hugo; Martini, Rose; Chevignard, Mathilde (Australian Occupational Therapy Journal, 2025)
Introduction: Children with acquired brain injury (ABI) often have executive function (EF) deficits that affect their ability to carry out activities efficiently. Cognitive Orientation to daily Occupational Performance (CO‐OP) is a cognitive approach to problem‐solving. It has demonstrated effectiveness in a variety of populations, most recently with children with EF deficits following ABI. One of the challenges of rehabilitation is transferring skills acquired during sessions into everyday life. The literature suggests that CO‐OP enables transfer of skills to untrained tasks, but research on transfer following its use with children with ABI is limited. The aims of this study were (1) to determine whether skills acquired during CO‐OP transfer to new untrained activities, (2) to study the possible influence of parental involvement in CO‐OP on children's attainment of transfer goals, and (3) to determine if the degree of difference between trained and untrained goals is associated with achievement of transfer. Methods: A quasi‐experimental design was used. Eleven children with EF deficits following ABI took part in the study. At the end of CO‐OP intervention, children identified three new goals. These 'transfer' goals were assessed at baseline (immediately post‐intervention) and at 2‐, 4‐ and 6‐month, using the Goal Attainment Scale (GAS) and the self‐ and parent‐rated Canadian Occupational Performance Measure (COPM). Children did not receive any specific intervention during this time. Consumer and Community Involvement: There was no consumer and community involvement. Results: At 6 months, GAS indicated that 22 of 32 transfer goals had improved by at least one level. COPM showed a significant increase in (1) child perception of performance and satisfaction for 24/31 and 25/31 goals, respectively, and (2) parent perception of performance and satisfaction for 19/29 of goals. Conclusion: This study showed that CO‐OP facilitates transfer of acquired skills to new, untrained activities, even after the end of the intervention. PLAIN LANGUAGE SUMMARY: The day begins with simple tasks like turning off the alarm, taking a shower, going to school, writing notes, playing with friends during recess, and going to gym class. But for children with an acquired brain injury (ABI), these tasks can be hard. ABI can cause problems with movement, focus, social skills, and planning. These problems make daily life more difficult. To help children with ABI, an approach called the Cognitive Orientation to daily Occupational Performance (CO‐OP) can be used. This is a type of therapy that helps children learn how to do daily tasks better. This study looked at how well children could use the skills they learned with CO‐OP for new tasks they had not practiced. It also looked at how parents helped during learning, and how different types of tasks affected what children could learn. Eleven children with brain injuries took part in this study. After CO‐OP, each child chose three new tasks they wanted to improve. These tasks were measured right after the intervention and again after 2, 4, and 6 months. After 6 months, 22 of the 32 new goals had improved. The children also felt they were doing better and were more satisfied with how they did 24 and 25 of 31 goals. Parents also saw progress in 19 of 29 goals. This study shows that CO‐OP helps children use new skills in everyday life. It also shows that this approach can give long‐term help for children with brain injuries. It supports using thinking‐based methods to help with problems in planning and focus.